BEHAVIOR OF ENTERPRISES REGARDING THE SOLUTION OF THE PROBLEM OF INTERACTION OF DEMAND AND SUPPLY - Линькова, Елена (SWorldJournal, 2021)
Analysis of the experience of supply and demand settlement during the COVID-19 pandemic is the basis of the proposed direction of organizational development through the management of organizational projects in the field of the selected business model. Ta